Perkembangan Sosial Anak Tenaga Kerja Wanita (TKW) : Studi Kasus pada Anak Usia SMP di Desa Panggul Trenggalek - Hazin Farika Yati; Bagus Setiawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research is motivated by the social problems of junior high school children in Panggul Village, Trenggalek, whose parents work as female migrant workers. The children show symptoms of lack of socialization, low self-confidence, and minimal emotional support from their mothers. This study aims to analyze the social competence and social responsibility of these children. The approach used is qualitative with a case study method. Informants consisted of 11 people, namely TKW husbands, substitute families, community leaders, and junior high school children. Data collection techniques include in-depth interviews, observation, and documentation. The results of this study indicate that junior high school children in Panggul Village who are left by their parents as TKW have the ability to interact with family, friends, and the community, but tend to have less understanding of the social conditions around them due to their indifference and lack of self-confidence. They are closed, have minimal empathy due to lack of role models from parents, and only show concern for peers. In terms of responsibility, these children have awareness of interacting with family, but still lack overall concern.